Natural variation and gene regulatory basis for the responses of asparagus beans to soil drought - Xu, Pei; Moshelion, Menachem; Wu, XiaoHua; Halperin, Ofer; Wang, BaoGen; Luo, Jie; Wallach, Rony; Wu, Xinyi; Lu, Zhongfu; Li, Guojing (Frontiers in Plant Science, 2015)
Asparagus bean (Vigna unguiculata ssp. sesquipedalis) is the Asian subspecies of cowpea, a drought-resistant legume crop native to Africa. In order to explore the genetic variation of drought responses in asparagus bean, we conducted multi-year phenotyping of drought resistance traits across the Chinese asparagus bean mini-core. The phenotypic distribution indicated that the ssp. sesquipedalis subgene pool has maintained high natural variation in drought responses despite known domestic bottleneck. Thirty-nine SNP loci were found to show an association with drought resistance via a genome-wide association study (GWAS). Whole-plant water relations were compared among four genotypes by lysimetric assay. Apparent genotypic differences in transpiration patterns and the critical soil water threshold in relation to dehydration avoidance were observed, indicating a delicate adaptive mechanism for each genotype to its own climate. Microarray gene expression analyses revealed that known drought resistance pathways such as the ABA and phosphate lipid signaling pathways are conserved between genotypes, while differential regulation of certain aquaporin genes and hormonal genes may be important for the genotypic differences. Our results suggest that divergent sensitivity to soil water content is an important mechanism configuring the genotypic specific responses to water deficit. The SNP markers identified provide useful resources for marker-assisted breeding.